Public support to firm-level innovation: An evaluation of the FONTAR program - Pereira, Mariano; Martínez Correa, Julián; Scattolo, Gabriel (Estudios de Economía, 2018)
This paper studies the impact of non-refundable grants (NRG) of the Argentinean Technological Fund (FONTAR) on firms’ innovative efforts and performance. We use a panel database of 954 firms that applied for public support to innovate during the period 2007-2013. Using a difference-in-differences approach, our results show that the NRG have a positive effect on firms’ innovative intensity, considering both the innovation activities to sales ratio and R&D to sales ratio. These remain robust to alternative definitions of control group and the outcome variable. Analysis of heterogeneous effects reveals that the impact was exclusively concentrated on small and young firms.